Country of origin and destination effects in buyer decision making: a relationship perspective - Vinhas da Silva, R. M. V.; Davies, G.; Naudé, P. (Journal of Business-to-Business Marketing, 2001)
Gaps between the perceptions of buyers and sellers on the relative strengths of competing purchasing options are likely to exist in any commercial market. In the case of international trade, one contributing factor is likely to be the Country of Origin effect, the stereotyping by buyers in one market of suppliers or products from another. While this effect has been studied, particularly in the context of consumer buying, no previous work exists comparing the gaps between the perceptions of commercial buyers in one country and the views held by suppliers in a second country. This research examines the buying decision making of UK retail buyers of textiles/clothing and compares it with the perceptions held by Portuguese textiles/clothing suppliers on how UK buyers make decisions when deciding between sourcing options in the two countries. The research methodology involves the use of a multi-criteria modelling technique (JAS). Buyers were asked to imagine that they were considering a ‘new buy,’ where they could source from either the UK or Portugal. Suppliers were asked to place themselves in the role of the buyers and to undertake the same methodology. The gaps in perception are discussed in the context of the Country of Origin effect and labelled as the Country of Destination effect.